Ameliorasi Lahan Berpasir sebagai Cara Pemulihan Lahan Berpasir Menjadi Sawah Produktif di Kebun Percobaan PT PIM - Sri Wahyuni; M. Aqiel; Nurul Ismi; Suci Mahdianti; Usman Usman; Fachrian Fachrian (Fakultas Teknik, 2023)
AbstractNorth Aceh Regency has 12,750 ha of unused land that has the potential to become rice cultivation. This unused land becomes a paddy field because it has a large enough area and contains elements needed by rice plants. PT Pupuk Iskandar Muda carried out a program to improve sandy land into fertile rice fields called AMELASIR (Ameliorasi Lahan Berpasir) with a plot of 278 m2. This program is carried out by offering an ameliorant and intensive tillage. The ingredients added are PIM organic fertilizer, clay, manure, rice straw compost, Polivit PIM, and Urea PIM. The results of this program indicate an increase in rice yields from year to year. In the first planting season, the harvest reached 3 tons/ha, in the second planting season, it reached 3.45 tons/ha, and in the third planting season, the harvest reached 4.5 tons/ha. This area has an index of fauna biodiversity H’ 3,22 and flora biodiversity H’ 2,28. The conversion from unused land to paddy fields also increases biodiversity, attracting several fauna species, namely 12 birds, one reptile species, two mammal species, and 20 insect species. The AMELASIR program also causes the soil to become more fertile for some trees, so four species of trees, two species of poles, eight species of saplings, and 16 species of seedlings grow in the area.Keywords: amelioration, sand, paddy field, biodiversity, species